The Limits of Labour: Class Formation and the Labour Movement in Calgary, 1883-1929 - Seager, Allen (Labour / Le Travail, 2000)
The article reviews the book, "The Limits of Labour: Class Formation and the Labour Movement in Calgary, 1883-1929," by David Bright.